Status of beedi rollers in urban slum area of Dharwad city, India - Kollur, Lata Radhakrishna; Shetty, Akshath Kumar; Kongwad, Drakshayani Pandurang; Chowti, Jayprakash (International Journal Of Community Medicine And Public Health, 2017)
Background:Beedi is also called as poor man’s cigarette. Government estimates total number of beedi workers at about 4.5 million. Women involvement in beedi rolling has been linked to the ease of learning skill, its manual operations, the fact that work can be carried out at home. Beedi rollers are exposed to unburnt tobacco dust through cutaneous and pharyngeal route. Methods: Community adopted under UHTC, Dept. of Community medicine, SDMCMS&H, Dharwad, Karnataka. All beedi rollers residing in the Community adopted under UHTC who were involved in beedi rolling since at least last 6 months and willing to participate in the study. Study duration was 2 months (April to June 2014). Preformed pretested questionnaire was used to collect data regarding sociodemographic profile, health problems and knowledge, attitude and practices towards handling of tobacco, urine cotinine test strips. Ethical clearance was obtained from Institutional ethical committee of SDMCMS&H, Dharwad. Descriptive statistics like percentages and proportions were calculated. Results:All participants in our study were females and mean age at starting beedi rolling was 15 years. Commonest reason for starting beedi rolling was to support family income. Regarding harmful effects of handling tobacco dust for rolling beedi, 5 (17%) participants replied positively, whereas remaining 24 (82.7%) participants considered it to be harmless. Washing hands after handling tobacco dust was a common practice of 19 (65.5%) participants. Conclusions:Handling tobacco dust is considered harmless by beedi rollers mainly because of ignorance which arises due to illiteracy and becomes their need to support family economically.